2008
DOI: 10.1177/1420326x08092043
|View full text |Cite
|
Sign up to set email alerts
|

Size Distributions of the Aerosols Emitted from Commercial Cooking Processes

Abstract: Exposure to cooking fumes may be responsible for respiratory health effects. However, the linkage between such exposures and these effects cannot be established without knowing the size distribution of the aerosols emitted from cooking activities. This study examined the size distribution of the aerosols generated by commercial cooking processes. It was found that the aerosol size distributions were lognormal. Several theoretical models can explain the lognormal characteristic of aerosols from cooking processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 33 publications
5
46
0
2
Order By: Relevance
“…For instance, Wallace et al (2008) conducted an intensive measurement and believed that the majority of the particles emitted from cooking were less than 10 nm with the peak concentration occurring around 5 nm to 6 nm. Yeung and To (2008) draw a conclusion that size distribution of particles followed a lognormal distribution and the diameter increased as cooking temperature increased. Attention was also focused on ultrafine particles (UFPs, diameter < 100 nm) from cooking as they can affect the human health more than larger particles.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, Wallace et al (2008) conducted an intensive measurement and believed that the majority of the particles emitted from cooking were less than 10 nm with the peak concentration occurring around 5 nm to 6 nm. Yeung and To (2008) draw a conclusion that size distribution of particles followed a lognormal distribution and the diameter increased as cooking temperature increased. Attention was also focused on ultrafine particles (UFPs, diameter < 100 nm) from cooking as they can affect the human health more than larger particles.…”
Section: Introductionmentioning
confidence: 95%
“…This might be due to the existence of water vapor droplets during boiling, as suggested by See and Balasubramanian (2006). In contrast, frying generated more submicron-sized particles than boiling, and the emitted aerosols were less volatile (remaining in particle state) and more easily coagulated (Yeung and To, 2008). These growing particles settled during transportation to the adjoining room.…”
Section: Particle Number Concentrationmentioning
confidence: 99%
“…For instance, on the basis of cooking temperature, Yeung and To (2008) found that aerosol peak number concentrations occurred in the 100-160 nm range and that at higher cooking temperatures, the aerosol mode diameter increased. Moreover, in their experiments, bimodal distributions of submicron-sized aerosols could be expected to be generated.…”
Section: Introductionmentioning
confidence: 99%
“…Such assumed source was insufficient to obtain the actual exposure concentration. A number of studies (Siegmann and Sattler, 1996;He et al, 2004;Yeung and To, 2008;Wallace et al, 2008;Buonanno et al, 2009;Zhang et al, 2010;Diapouli et al, 2011) have attempted to measure the number concentration of indoor particles during cooking activities. Their measuring points were located a certain distance away from the source to represent the wellmixed concentration in the space.…”
Section: Introductionmentioning
confidence: 99%